Student Decision Choosing Management Program at Sekolah Tinggi Ilmu Ekonomi Tuah Negeri - Meri Yanti; Naswa Harika; Yosefine Indria Angreini (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
Sekolah Tinggi Ilmu Ekonomi Tuah Negeri has to constantly put first professionalism when pursuing its mission to advance higher education. Obviously, every effort is made to ensure that this educational institution is accepted by the community. Observing the increasing interest of prospective students is a top priority. Examining this is crucial because it relates to the expansion of postsecondary education as the nation's primary mode of instruction. This study will examine the influence of product, price, location, and advertising on students' selection of Sekolah Tinggi Ilmu Ekonomi Tuah Negeri. Students from the Management Programme contribute to the population of the study. Using the Leedy formula, one hundred respondents comprise the sample. Utilizing the confidence sampling technique, the sample is determined. Utilizing the Classical Assumption Test to analyze data. All of the evaluated factors had a significant impact on the selection of Sekolah Tinggi Ilmu Ekonomi Tuah Negeri by students.